Active energy ray-curable composition for forming hard coat layer on transparent substrate, hard coat film using the same and laminate thereof
Patent Information
- Application Number
- JP2024019916
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-02-14
- Publication Date
- 2025-03-07
AI Technical Summary
【0022】 本発明により、ディスプレイ生産プロセス中の傷付き、硬化収縮によるカール発生、およびけん化処理液に対する紫外線カット剤の溶出を抑えたハードコート層形成用活性エネルギー線硬化型組成物、それを用いたハードコートフィルムおよびその積層体を提供することが出来る。
Smart Images

Figure 2025031478000001 
Figure 2025031478000002 
Figure 2025031478000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an active energy ray-curable composition for forming a hard coat layer on a transparent substrate, a hard coat film using the same, and a laminate thereof.
[0002] More specifically, the present invention relates to an active energy ray-curable composition for forming a hard coat layer, which can be applied to displays such as TVs, notebook computers, mobile phones, and smartphones, a hard coat film using the same, and a laminate thereof. [Background technology]
[0003] In addition to the liquid crystal displays (LCDs) that have traditionally been widely used for display applications such as TVs, laptops, mobile phones, and smartphones, various other displays have been developed and products that take advantage of their various features are being introduced to the market.
[0004] Among these, organic electroluminescence (EL) displays are rapidly expanding into a variety of applications such as TVs and smartphones. However, the light-emitting elements used in organic EL displays are vulnerable to water vapor and impurity gases generated from the constituent materials. To prevent deterioration due to water vapor, an inorganic compound barrier layer (inorganic layer) is provided on the substrate, and to protect the light-emitting elements against impurity gases, volatile components are reduced, etc. In addition, the display is also greatly affected by external factors such as heat and ultraviolet rays, and the effects of ultraviolet rays in particular are not limited to the high energy region on the low wavelength side, but even ultraviolet rays with a wavelength of around 400 nm, which is close to visible light, can have a significant degrading effect. Therefore, when considering outdoor use, a function to block ultraviolet rays is required to protect the internal structure from ultraviolet rays that enter the display from outside. On the other hand, polarizing plates are laminated on general OLED displays. The polarizing plates used in OLED displays are called circular polarizing plates, and are different from those used in LCD displays for controlling light transmission. Metal is used in the electrode parts that make up OLED displays, and external incident light is scattered inside the display at these electrode parts. Circular polarizing plates are laminated to avoid the effects of this external incident light.
[0005] Conventionally, polarizing plates have often been made of water-soluble polyvinyl alcohol (PVA) because of its compatibility with liquid crystals, and are manufactured by dyeing with iodine and stretching it into a film. Because PVA polarizing plates are hygroscopic, triacetyl cellulose (TAC) film, which has excellent flame resistance, appearance (transparency), and insulation properties, is used as a protective film.
[0006] When adhering a polarizing plate made from PVA to a TAC film, the surface of the TAC film must be saponified with caustic alkali to hydrolyze some of the acetyl groups (-O=COCH groups) on the surface of the TAC film into hydrophilic hydroxyl groups (-OH).
[0007] The saponification process for TAC film is carried out by immersing the TAC film in an alkaline aqueous solution such as sodium hydroxide (NaOH) or potassium hydroxide (KOH). When polarizing a display, a hard coat (HC), anti-glare (AG), anti-reflection (AR), antistatic (AS), or other functional layer is often laminated on the surface opposite to the polarizing plate. These functional layer lamination processes are generally carried out before the saponification treatment using caustic alkali in order to maintain adhesion between the PVA polarizer and the TAC film. Therefore, after the functional layers are laminated, a saponification treatment using a strong alkali is carried out, which damages the functional layers that have been laminated and causes problems such as a decrease in functionality.
[0008] Furthermore, devices with displays, especially mobile devices such as laptops, mobile phones, smartphones, pads, and smartwatches, are becoming lighter and smaller in size because of the emphasis on portability, and efforts are being made to multi-function and thin the functional layers in the display configuration. In the study of thinning, progress is being made in reducing the thickness of the base film, and thin films from 100 μm to less than 50 μm are also being considered. When an active energy ray-cured material is applied onto a film, generally, curing shrinkage occurs, causing warping and curling. This tendency becomes more pronounced as the film substrate becomes thinner. Since displays are constructed by laminating functional layers, curling of the substrate after the formation of the functional layers leads to poor workability in subsequent processes and reduced yields.
[0009] Patent documents 1 and 2 exemplify a transparent double-sided adhesive sheet that has at least one ultraviolet absorbing layer and reduces the transmittance of light at a wavelength of 380 nm and is disposed between the viewing side of a polarizing plate layer and the display section of an organic EL display to integrate the two components as an attempt to make functional layers in a display structure multifunctional and thin them.
[0010] However, when adding an ultraviolet-blocking agent to a double-sided adhesive sheet, there is an inherent limit to the amount that can be added in order to prevent bleeding and maintain adhesive performance. As a result, by making the component thinner, it was not possible to adequately block ultraviolet light entering the display area, and it was not possible to prevent adverse effects on the display.
[0011] On the other hand, when a UV-cutting functional layer is laminated on the opposite side of the TAC film that is in close contact with the PVA polarizing plate, the saponification treatment of the TAC film may cause the UV-cutting agent to leach out of the UV-cutting functional layer, resulting in an increase in UV transmittance and leach (contamination) of the UV-cutting agent into the saponification treatment solution. As a countermeasure, Patent Document 3 exemplifies a treatment method in which only the side of the TAC film opposite to the side on which the ultraviolet-curing functional layer is provided is selectively saponified, but the effect of saponification on the ultraviolet-cutting layer could not be eliminated. Furthermore, increasing the crosslink density of the functional layer causes problems such as curling due to curing shrinkage. It is possible to apply a protective film during the saponification treatment, but this may cause problems such as deterioration and increased costs due to the increased number of steps. On the other hand, the effect of the ultraviolet-cutting agent on ultraviolet curing must also be suppressed, and improvements are still required.
[0012] In addition, because TAC film has high moisture permeability, polarizing plates to which the TAC film is attached as a protective film have the problem of deteriorating under conditions of high humidity and heat, for example, a temperature of 70°C and a relative humidity of 90%. Therefore, a method has been proposed to solve this problem by using a resin film with lower moisture permeability than the TAC film as a protective film. For example, it is known to use a polyethylene terephthalate resin film or an acrylic resin film as a protective film.
[0013] Even when a material other than TAC film is used as the protective film, it is produced on the same production line as the TAC film, and may come into contact with the above-mentioned saponification treatment solution, which may cause the UV-blocking agent to leach out (become contaminant) into the saponification treatment solution. [Prior art documents] [Patent documents]
[0014] [Patent Document 1] JP 2012-211305 A [Patent Document 2] JP 2022-000694 A [Patent Document 3] JP 2007-308670 A [Patent Document 4] International Publication No. 2020 / 209264 Summary of the Invention [Problem to be solved by the invention]
[0015] The present invention provides an active energy ray-curable composition for forming a hard coat layer on a transparent substrate, which is suppressed in terms of scratches during the display production process, curling due to curing shrinkage, and elution of an ultraviolet ray blocking agent into a saponification treatment solution, and a hard coat film and a laminate thereof using the same. [Means for solving the problem]
[0016] As a result of intensive research into the above-mentioned problems, the present inventors discovered that the problems could be solved by using the active energy ray-curable composition described below, and thus completed the present invention.
[0017] The present invention relates to an active energy ray-curable composition for forming a hard coat layer on a transparent substrate, comprising an active energy ray-curable component (A), an ultraviolet ray-blocking agent (B), a photopolymerization initiator (C) and a solvent (D), wherein the active energy ray-curable component (A) comprises all of the following (a1), (a2) and (a3), the molecular weight of the ultraviolet ray-blocking agent (B) is 300 or more, and the photopolymerization initiator (C) comprises at least one of an oxime ester compound and a phosphine oxide compound: (a1) A polyfunctional urethane (meth)acrylate having six or more (meth)acryloyl groups and a nurate ring skeleton. (a2) A polyfunctional urethane (meth)acrylate having 4 to 15 (meth)acryloyl groups and a weight average molecular weight of 500 to 15,000 (excluding (a1)). (a3) Other polyfunctional (meth)acrylates
[0018] The present invention also relates to a hard coat film having a hard coat layer, which is a cured product of the active energy ray-curable composition, on a transparent substrate.
[0019] The present invention also relates to the hard coat film, which has a transmittance (ta) at a wavelength of 380 nm of 4% or less and a transmittance (tb) at a wavelength of 420 nm of 70% or more.
[0020] The present invention also relates to the hard coat film, which satisfies the following formula (2): Equation (2) (tc)-(ta)≦1% (ta): Transmittance at a wavelength of 380 nm of a hard coat film not immersed in a sodium hydroxide aqueous solution (tc): Transmittance of the hard coat film at a wavelength of 380 nm after immersion in an aqueous solution of sodium hydroxide, washing with water and drying.
[0021] The present invention also relates to a laminate having the hard coat film and a circularly polarizing functional layer. Effect of the Invention
[0022] The present invention can provide an active energy ray-curable composition for forming a hard coat layer that suppresses scratches during the display production process, curling due to curing shrinkage, and elution of an ultraviolet ray blocking agent into a saponification treatment solution, as well as a hard coat film and a laminate thereof using the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] The present invention will be described in detail below. Needless to say, other embodiments are also included in the scope of the present invention as long as they are consistent with the gist of the present invention. In addition, in this specification, a numerical range specified using "~" includes the numerical values before and after "~" as the lower and upper limit ranges.
[0024] First, the terms used in this specification will be explained. In this specification, unless otherwise specified, the terms "(meth)acrylic", "(meth)acryloyl", and "(meth)acrylate" mean "acrylic or methacrylic", "acryloyl or methacryloyl", and "acrylate or methacrylate", respectively. In addition, "active energy ray curable composition for forming a hard coat layer on a transparent substrate" may be referred to as "hard coat layer forming composition", "(a1) urethane acrylate having 6 or more (meth)acryloyl groups and having a nurate ring skeleton" may be referred to as "urethane acrylate (a1)", "(a2) polyfunctional urethane acrylate (excluding (a1)) having 4 to 15 (meth)acryloyl groups and having a weight average molecular weight of 500 to 15,000" may be referred to as "polyfunctional urethane acrylate (a2)", and "(a3) other polyfunctional acrylate" may be referred to as "polyfunctional acrylate (a3)". Unless otherwise noted, each of the various components appearing in this specification may be used independently alone or in a mixture of two or more.
[0025] <Active energy ray-curable component (A)> The active energy ray-curable component (A) contains all of the following (a1), (a2) and (a3). (a1) A polyfunctional urethane (meth)acrylate having six or more (meth)acryloyl groups and a nurate ring skeleton. (a2) A polyfunctional urethane (meth)acrylate having 4 to 15 (meth)acryloyl groups and a weight average molecular weight of 500 to 15,000 (excluding (a1)). (a3) Other polyfunctional (meth)acrylates The polyfunctional urethane (meth)acrylate refers to an oligomer having a urethane bond and two or more (meth)acrylate groups.
[0026] <Polyfunctional urethane (meth)acrylate (a1)> The urethane (meth)acrylate (a1) has six or more (meth)acryloyl groups and a nurate ring skeleton. The nurate ring skeleton is a trimer of an isocyanate compound having a nitrogen atom, and has a six-membered ring structure. By having six or more (meth)acryloyl groups, the crosslink density is increased, and the hard coat film surface has excellent hardness and scratch resistance, and the hard coat film can be prevented from curling. Although the detailed factors that prevent curling are unknown, it is believed that the ring structure of the nurate ring skeleton portion contributes greatly to stress relaxation. Compounds having three (meth)acryloyl groups and a nurate ring skeleton are also relatively easy to obtain, but are not suitable because the hardness and scratch resistance of the hard coat film surface are insufficient due to their low crosslink density.
[0027] Specific examples of the urethane (meth)acrylate (a1) include a reaction product of an isocyanurate (trimer) of a diisocyanate with a poly(meth)acrylate compound having a hydroxyl group, and a reaction product of an isocyanurate (trimer) of a polyisocyanate with a polyol and a poly- or mono(meth)acrylate compound having a hydroxyl group. From the viewpoint of excellent hardness and scratch resistance of the hard coat film surface, a reaction product of an isocyanurate (trimer) compound of a diisocyanate with a poly(meth)acrylate compound having one hydroxyl group and two or more (meth)acryloyl groups is preferred.
[0028] Examples of diisocyanates include aromatic diisocyanates such as tolylene diisocyanate, xylylene diisocyanate, and diphenylmethane diisocyanate, hydrogenated products of the above aromatic isocyanates, and aliphatic diisocyanurates such as isophorone diisocyanate and hexamethylene diisocyanate. Examples of mono(meth)acrylates having one hydroxyl group include 2-hydroxyethyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate, and 4-hydroxypropyl(meth)acrylate. Dibutyl (meth)acrylate, etc. Examples of poly(meth)acrylates having one hydroxyl group include, but are not limited to, pentaerythritol tri(meth)acrylate and dipentaerythritol penta(meth)acrylate.
[0029] The polyols include, but are not limited to, ethylene glycol, polyethylene glycol, polypropylene glycol, glycerin, trimethylolpropane, cyclohexanediol, cyclohexanedimethanol, and tricyclodecane dimethanol.
[0030] <Polyfunctional urethane (meth)acrylate (a2)> The polyfunctional urethane (meth)acrylate (a2) is a polyfunctional urethane (meth)acrylate (excluding (a1)) having 4 to 15 (meth)acryloyl groups and a weight average molecular weight of 500 to 15,000. The weight average molecular weight is preferably 1,000 to 5,000. The weight average molecular weight (Mw) is a polystyrene-equivalent weight average molecular weight determined by gel permeation chromatography (GPC) measurement. The weight average molecular weight can be measured by the method described in the [Examples] section.
[0031] The polyfunctional urethane (meth)acrylate (a2), when used in combination with the urethane (meth)acrylate (a1), can achieve a balance between crosslink density, flexibility, and adhesion to the substrate, and can reduce scratches, curling (warping), and elution and deterioration of the UV-blocking agent.
[0032] Examples of the polyfunctional urethane (meth)acrylate (a2) include those obtained by reacting a polyisocyanate with a mono(meth)acrylate or poly(meth)acrylate having a hydroxyl group, and those obtained by reacting an isocyanate group-containing urethane prepolymer obtained by reacting a polyol with a polyisocyanate under conditions of an excess of isocyanate groups with a mono(meth)acrylate or poly(meth)acrylate having a hydroxyl group. Alternatively, it can be obtained by reacting a hydroxyl group-containing urethane prepolymer obtained by reacting a polyol with a polyisocyanate under conditions of excess hydroxyl groups with a (meth)acrylate having an isocyanate group.
[0033] The following describes a method for producing the urethane (meth)acrylate (a2), but it is by way of example and is not intended to be limiting. For example, the urethane (meth)acrylate (a2) can be obtained by stirring a polyisocyanate and a hydroxyl group-containing (meth)acrylate in the presence of a suitable urethane-forming catalyst under an oxygen atmosphere at 60 to 100°C for 4 to 8 hours. Specific examples of urethane catalysts include copper naphthenate, cobalt naphthenate, zinc naphthenate, dibutyltin dilaurate, triethylamine, 1,4-diazabicyclo[2.2. 2]octane, 2,6,7-trimethyl-1,4-diazabicyclo[2.2.2]octane, etc. Among these, dibutyltin dilaurate, etc. are particularly preferred.
[0034] Examples of the polyisocyanate include aliphatic diisocyanates and aromatic diisocyanates. Examples of the aliphatic diisocyanate include hexamethylene diisocyanate, isophorone diisocyanate, hydrogenated xylylene diisocyanate, and hydrogenated diphenylmethane diisocyanate. Examples of the aromatic diisocyanate include toluene diisocyanate, xylylene diisocyanate, and diphenylmethane diisocyanate. The bonding position of the isocyanate group with the aromatic group may be any of the ortho, meta, and para positions. The diisocyanate may also form an isocyanurate ring as a trimer. . Among these, aliphatic diisocyanates are preferred from the viewpoint of suppressing yellowing when optical applications are envisaged.
[0035] The (meth)acryloyl number and weight average molecular weight can be adjusted by the combination of polyol, polyisocyanate, and hydroxyl group-containing mono(meth)acrylate or poly(meth)acrylate.
[0036] Hydroxyl-containing (meth)acrylates include trimethylolpropane di(meth)acrylate. acrylate, trimethylolethane di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, 2-hydroxyethyl (meth)acrylate, 1-hydroxypropyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 1-hydroxybutyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, Examples of the hydroxyl group-containing (meth)acrylic acid ester include 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, cyclohexanedimethanol mono(meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, ethyl-α-(hydroxymethyl) (meth)acrylate, monofunctional glycerol (meth)acrylate, or (meth)acrylic acid esters having a hydroxyl group at the end obtained by ring-opening addition of these (meth)acrylates to ε-caprolactone lactone, and alkylene oxide-added (meth)acrylic acid esters obtained by repeatedly adding alkylene oxides such as ethylene oxide, propylene oxide, and butylene oxide to the above-mentioned hydroxyl group-containing (meth)acrylates. From the viewpoint of increasing the crosslink density and suppressing scratches, curling, elution of ultraviolet blocking materials, etc., a (meth)acrylic acid ester having 2 to 5 (meth)acrylolyl groups is preferred. Specifically, it is preferred to include at least one selected from trimethylolpropane di(meth)acrylate, trimethylolethane di(meth)acrylate, pentaerythritol tri(meth)acrylate, and dipentaerythritol penta(meth)acrylate.
[0037] Examples of urethane acrylates (a2) whose molecular weight and number of acryloyl groups are published in catalogs, etc., include Mitsubishi Chemical Corporation's Shiko UV1700B (molecular weight 2000, number of acryloyl groups 10), UV7600B (molecular weight 1400, number of acryloyl groups 6), UV7605B (molecular weight 1100, number of acryloyl groups 6), UV7610B (molecular weight 1100, number of acryloyl groups 9), and UV7629E. A (molecular weight 4100, number of acryloyl groups 9, volatile content 35%), UV7640B (molecular weight 1500, number of acryloyl groups 6-7), and UV7650B (molecular weight 2300, number of acryloyl groups 4-5); MIWON Co., Ltd.: Miramer PU610 (molecular weight 1800, number of acryloyl groups 6), and MU9500 (molecular weight 3200, number of acryloyl groups 10); Nippon Kayaku Co., Ltd.: KAYARAD DPHA-40H (molecular weight 2000, number of acryloyl groups 10), UX-5000 (molecular weight 1500, number of acryloyl groups 6), UX-5102D-M20 (molecular weight 3500, number of acryloyl groups 6) Examples of the resins that can be used include, but are not limited to, Art Resin UN-3320HA (molecular weight 1500, number of acryloyl groups 6), UN-3320HC (molecular weight 1500, number of acryloyl groups 15, volatile content 5%), UN-904 (molecular weight 4900, number of acryloyl groups 10), UN-906S (molecular weight 1000, number of acryloyl groups 6), UN-901T (molecular weight 4000, number of acryloyl groups 9, volatile content 20%), and UN-952 (molecular weight 6500 to 11000, number of acryloyl groups 10), manufactured by Negami Chemical Industries, Ltd.
[0038] <Polyfunctional (meth)acrylate (a3)> The polyfunctional (meth)acrylate (a3) is a polyfunctional (meth)acrylate other than (a1) and (a2). Examples of the polyfunctional (meth)acrylate (a3) include, but are not limited to, various diol (meth)acrylates, trimethylolethane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, various polyol poly(meth)acrylates such as pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate, tri(meth)acrylates of isocyanurates of various diisocyanates, and urethane acrylates other than the polyfunctional urethane acrylate (a1) and the polyfunctional urethane acrylate (a2). The pentaerythritol triacrylate (a3-1), pentaerythritol tetraacrylate (a3-2), dipentaerythritol pentaacrylate (a3-3), and dipentaerythritol hexaacrylate (a3-4) remaining during the synthesis of the urethane (meth)acrylate (a1) and the urethane (meth)acrylate (a2) can be used as they are.
[0039] Examples of urethane acrylates other than the polyfunctional urethane acrylate (a1) and the polyfunctional urethane acrylate (a2) include polyfunctional acrylates having 2 to 5 (meth)acryloyl groups and a nurate ring skeleton, and polyfunctional urethane acrylates having a number of (meth)acryloyl groups outside the range of 4 to 15 or a weight average molecular weight outside the range of 500 to 15,000.
[0040] Examples of polyfunctional acrylates having 2 to 5 (meth)acryloyl groups and a nurate ring skeleton include: Toagosei Co., Ltd.: Aronix M-215 and other isocyanuric acid EO modified diacrylates (2 acryloyl groups), Isocyanuric acid EO-modified diacrylate and / or triacrylate (with 2 to 3 acryloyl groups) such as Aronix M-313 (Toagosei Co., Ltd.) and Aronix M-315 (Toagosei Co., Ltd.), Shin-Nakamura Chemical Co., Ltd.: NK Ester A-9300-1CL and other ε-caprolactone-modified (2-acryloxy) isocyanurates (with 3 acryloyl groups); Shin-Nakamura Chemical Co., Ltd.: NK Ester A-9300, Arkema Co., Ltd.: SARTOMER Examples of the tris(2-acryloxyethyl)isocyanurate (having 3 acryloyl groups) include, but are not limited to, SR368 manufactured by Daiichi Kogyo Seiyaku Co., Ltd., NEW FRONTIER TEICA (GX-8430) manufactured by Daiichi Kogyo Seiyaku Co., Ltd., and FANCRYL FA-731A manufactured by Showa Denko Co., Ltd.
[0041] Examples of polyfunctional urethane acrylates having a number of (meth)acryloyl groups outside the range of 4 to 15 or a weight average molecular weight outside the range of 500 to 15,000 include: Examples of urethane acrylates include, but are not limited to, Shikoh UV-6300B (molecular weight 3700, number of acryloyl groups 3) manufactured by Mitsubishi Chemical Corporation, Art Resin UN-5500 (molecular weight 50000, number of acryloyl groups 12.5, volatile content 50%), UN-5507 (molecular weight 17000, number of acryloyl groups 15.5, volatile content 50%), and UN-905 (molecular weight 40000 to 200000, number of acryloyl groups 15, volatile content 40%) manufactured by Negami Chemical Industries Co., Ltd., and Miramer SC2152 (molecular weight 20787, number of acryloyl groups 15) manufactured by MIWON Co., Ltd.
[0042] The mass ratio (a1) / (a2) of the multifunctional urethane (meth)acrylate (a1) and the multifunctional urethane (meth)acrylate (a2) contained in the active energy ray-curable component (A) is The (a1) / (a2) ratio is preferably 20 / 80 to 80 / 20, and more preferably 60 / 40 to 40 / 60. By setting the (a1) / (a2) ratio to 20 / 80 to 80 / 20, it is possible to suppress scratches during the process, elution of the UV-blocking agent, and adhesion to the substrate and curling.
[0043] The content of the polyfunctional urethane (meth)acrylate (a1), the polyfunctional urethane (meth)acrylate (a2) and the polyfunctional (meth)acrylate (a3) in 100% by mass of the active energy ray curable component (A) is preferably 12 to 48% by mass for the polyfunctional urethane (meth)acrylate (a1), 20 to 80% by mass for the polyfunctional urethane (meth)acrylate (a2), and 8 to 32% by mass for the polyfunctional (meth)acrylate (a3). By adjusting the content within this range, high scratch prevention, high substrate adhesion, suppression of curling, and suppression of elution of the ultraviolet ray blocking agent can be achieved.
[0044] <Ultraviolet ray blocking agent (B)> The ultraviolet ray blocking agent (B) is a material that absorbs ultraviolet rays. The molecular weight of the ultraviolet ray blocking agent (B) used is 300 or more. If the molecular weight is less than 300, it is not suitable because it is prone to leaching during the saponification process. The ultraviolet ray blocking agent (B) preferably has a molecular weight of 100,000 or less. If the molecular weight is 100,000 or less, the pencil hardness of the resulting hard coat film is excellent. In addition, from the viewpoints of preventing bleeding, preventing elution during the saponification step, cost, etc., it is preferable to use a material that has excellent ultraviolet absorbing ability even when added in a small amount. Examples of such ultraviolet ray blocking agents include benzotriazole-based, hydroxyphenyltriazine-based, and benzophenone-based ultraviolet ray blocking agents. Hydroxyphenyltriazine-based and benzotriazole-based UV cutters are preferred in terms of minimizing adverse effects on other physical properties of the coating film. The UV cutter may be a commercially available product as is, or two or more types of commercially available products may be mixed and used. Examples of commercially available UV cutters include the "TINUVIN" series (benzotriazole-based and hydroxyphenyltriazine-based) and "CHIMASSORB" series manufactured by BASF Co., Ltd., the "UVINUL" series (benzophenone-based and triazine-based) manufactured by BASF Co., Ltd., the "RUVA" series (benzotriazole-based) manufactured by Otsuka Chemical Co., Ltd., the "ADEGASTAVE LA" series (benzotriazole-based and triazine-based) manufactured by ADEKA Co., Ltd., the "Eversorb" series (benzotriazole-based, triazine-based, benzophenone-based) manufactured by Ever Light Chemicals, and the "Vanaresin UVA" series (benzotriazole-based, etc.) manufactured by Shin-Nakamura Chemical Co., Ltd.
[0045] The content of the ultraviolet ray blocking agent (B) is, for example, 0.5 to 20 mass%, preferably 2 to 15 mass%, relative to 100 mass% of the active energy ray curable component (A). By setting the content to 0.5 to 20 mass%, ultraviolet rays necessary for photoexciting the photopolymerization initiator can be secured while sufficient ultraviolet rays are blocked, and the curability of the coating film can be improved.
[0046] <Photopolymerization initiator (C)> The photopolymerization initiator (C) contains at least one of an oxime ester compound and a phosphine oxide compound.
[0047] The active energy ray curable composition of the present invention contains an ultraviolet ray cutter, thereby cutting ultraviolet rays with wavelengths of about 400 nm, which are close to visible light and affect the laminate, and therefore also cuts ultraviolet rays necessary for photoexcitation of the photopolymerization initiator. Therefore, the composition contains at least one highly sensitive initiator selected from oxime ester compounds and phosphine oxide compounds, which can efficiently generate radicals even with as little and slight ultraviolet rays as possible.
[0048] Specifically, phosphine oxide compounds such as 2,4,6-trimethylbenzoindiphenylphosphine oxide, and oxime ester compounds such as Irgacure OXE01, Irgacure OXE02, and Irgacure OXE03 manufactured by BASF Ltd. are preferred, and the use of oxime ester compounds is particularly preferred.
[0049] The amount of the photopolymerization initiator (C) is preferably 0.1 to 30% by mass, more preferably 5 to 20% by mass, based on 100% by mass of the total of the active energy ray-curable components (A). Within this range, a sufficient polymerization initiation effect is obtained, which is effective in improving adhesion and scratch resistance.
[0050] Further, photopolymerization initiators other than the oxime ester compounds and the phosphine oxide compounds may be used in combination. Other photopolymerization initiators are not particularly limited as long as they have the function of initiating radical polymerization by photoexcitation, and examples thereof include acetophenone compounds, benzoin compounds, benzophenone compounds, phosphine oxide compounds, ketal compounds, anthraquinone compounds, and thioxanthone compounds. Specific examples include benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin butyl ether, diethoxyacetophenone, benzil dimethyl ketal, 1-hydroxycyclohexyl phenyl ketone, benzophenone, 4,4'-bis(dimethylamino)benzophenone, 4,4'-bis(diethylamino)benzophenone, 2,4,6-trimethylbenzoin diphenylphosphine oxide, N,N-dimethylaminobenzoate isoamyl, 2-chlorothioxanthone, and 2,4-diethylthioxanthone. When used alone, the thioxanthone compound functions as a photopolymerization initiator, but when used in combination with other photopolymerization initiators, it also functions as a photosensitizer.
[0051] <Solvent (D)> The active energy ray-curable composition for forming a hard coat layer of the present invention may be diluted with a solvent. Known solvents can be used, such as dimethyl carbonate, ethyl acetate, n-butyl acetate, acetone, methyl ethyl ketone, 1,3-dioxolane, methyl isobutyl ketone, isopropyl alcohol, etc. Examples include, but are not limited to, polyvinyl alcohol, propylene glycol monomethyl ether, and propylene glycol monomethyl ether acetate.
[0052] The solvent (D) is preferably 40 to 80 mass %, more preferably 40 to 70 mass %, and even more preferably 45 to 65 mass %, of 100 mass % of the active energy ray-curable component (A) for forming a hard coat layer. When it is 40 mass % or more, the substrate permeability is high and the adhesion is further improved, and when it is 80 mass % or less, the substrate permeability is not too high and the deterioration of the coating haze or scratch resistance can be further suppressed.
[0053] <Sensitizer (F)> The composition for forming a hard coat layer in the present invention can use a photopolymerization initiator (C) and a sensitizer in combination. Examples of the sensitizer include amine-based sensitizers, anthracene-based sensitizers, and thioxanthone-based sensitizers. The sensitizers can be used alone or in combination of two or more kinds. Examples of the amine sensitizer include trimethylamine, methyldimethanolamine, triethanolamine, p-diethylaminoacetophenone, ethyl p-dimethylaminobenzoate (EPA), isoamyl p-dimethylaminobenzoate, ethyl 4-dimethylaminobenzoate, N,N-dimethylbenzylamine, and 4'-bis(diethylamino)benzophenone. Anthracene sensitizers include, for example, 9,10-dibutoxyanthracene (DBA), 9, Examples thereof include 10-diethoxyanthracene (DEA), 9,10-dipropoxyanthracene, and 9,10-bis(2-ethylhexyloxy)anthracene. Examples of the thioxanthone sensitizer include 2,4-diethylthioxanthone (DETX), 2-isopropylthioxanthone (ITX), and 4-isopropylthioxanthone. Representative examples of commercially available products include amine-based sensitizers such as KAYACURE KAYACURE EPA manufactured by Nippon Kayaku Co., Ltd., anthracene-based sensitizers such as Anthracure UVS-1331 (DBA) and UVS-1101 (DEA) manufactured by Air Water Performance Chemical Inc., and thioxanthone-based sensitizers such as Omnirad DETX and ITX manufactured by IGM Resins BV. Sensitizers having absorption up to about 420 nm, which is longer than the ultraviolet ray cutoff range, are preferred, and thioxanthone sensitizers or a combination of an amine sensitizer and a thioxanthone sensitizer are preferred.
[0054] When a sensitizer is used, its content is preferably from 1 to 15% by mass relative to 100% by mass of the active energy ray-curable component (A).
[0055] [Active energy ray-curable composition for forming a hard coat layer on a transparent substrate (composition for forming a hard coat layer)] The composition for forming a hard coat layer of the present invention contains an active energy ray-curable component (A), an ultraviolet ray blocking agent (B), a photopolymerization initiator (C) and a solvent (D).
[0056] The composition for forming a hard coat layer in the present invention may contain other additives as necessary, such as a plasticizer, a surface conditioner, a light stabilizer, an antioxidant, and a polymerization inhibitor.
[0057] [Hard coat film] The hard coat film of the present invention has a hard coat layer formed by curing the above-mentioned composition for forming a hard coat layer on a transparent substrate. The hard coat film of the present invention preferably has a transmittance (ta) of 4% or less at a wavelength of 380 nm and a transmittance (tb) of 70% or more at a wavelength of 420 nm. The transmittance (tb) at a wavelength of 420 nm is more preferably 75% or more, and even more preferably 80% or more, from the viewpoint of suppressing yellowing. With a transmittance (ta) of 4% or less at a wavelength of 380 nm, harmful ultraviolet rays to OLED displays with wavelengths of 380 nm or less are cut, preventing deterioration of the OLED display. Also, with a transmittance (tb) of 70% or more at a wavelength of 420 nm, accurate color reproduction of the OLED display is possible.
[0058] Furthermore, the hard coat film of the present invention preferably satisfies the following formula (2): (tc)-(ta)≦1% (2) (ta): Transmittance at a wavelength of 380 nm of a hard coat film not immersed in a sodium hydroxide aqueous solution (tc): Transmittance of the hard coat film at a wavelength of 380 nm after immersion in an aqueous solution of sodium hydroxide, washing with water and drying. By satisfying (tc)-(ta)≦1%, it is possible to reduce the elution of the UV-cutting agent into the saponification treatment solution while protecting the organic EL display from the harmful effects of ultraviolet light. The method for measuring (ta) and (tc) is described in detail in the [Examples] section.
[0059] <Transparent base material> The transparent substrate used in the present invention may be of any grade as long as it is optically transparent. Examples of resin films having a viscosity of 1.0% or less include amorphous polyolefin-based resin films, polyester-based resin films, polyethylene terephthalate (PET)-based resin films, acrylic-based resin films, polycarbonate (PC)-based resin films, polysulfone-based resin films, alicyclic polyimide-based resin films, polycycloolefin (COP)-based resin films, and triacetyl cellulose (TAC) films. Among these, polyethylene terephthalate-based resin films, acrylic-based resin films, polycarbonate-based resin films, and polycycloolefin-based resin films are preferred from the viewpoint of low moisture permeability.
[0060] The thickness of the transparent substrate is not particularly limited, but is generally about 10 to 500 μm from the standpoints of strength, ease of handling, thinness, etc. A thickness of 20 to 250 μm is particularly preferred.
[0061] <Manufacture of hard coat film> The method for producing the hard coat film is not particularly limited, and the hard coat film can be produced by a conventionally known method, such as coating a composition for forming a hard coat layer on a transparent substrate. For example, the composition for forming a hard coat layer of the present invention is applied to a transparent substrate, and then the solvent is dried as necessary. The applied composition for forming a hard coat layer is crosslinked and cured by irradiating the composition with active energy rays, thereby obtaining a hard coat film having a transparent substrate and a hard coat layer.
[0062] Examples of the coating method include bar coating, blade coating, spin coating, reverse coating, die coating, spray coating, roll coating, gravure coating, microgravure coating, lip coating, air knife coating, and dipping.
[0063] Examples of active energy rays that can be used include electron beams and ultraviolet rays emitted from light sources such as xenon lamps, low-pressure mercury lamps, high-pressure mercury lamps, extra-high-pressure mercury lamps, metal halide lamps, carbon arc lamps, and tungsten lamps.
[0064] The thickness of the hard coat layer is not particularly limited as long as it has hard coat properties, and is usually 1 to 20 μm, preferably 2 to 15 μm. The combined thickness of the hard coat layer and the mixed layer is also not particularly limited, but is preferably 0.5 to 100 μm, more preferably 1.1 to 30 μm, and even more preferably 1.2 to 25 μm in order to reduce interference unevenness. The thickness of the hard coat film is not particularly limited, but is preferably from 50 to 300 μm, more preferably from 81 to 100 μm, and further preferably from 82 to 95 μm.
[0065] [Laminate] The laminate of the present invention has a hard coat film and a circularly polarizing functional layer. The hard coat film and the circularly polarizing functional layer may be directly laminated, or another layer may be present between them. The embodiment in which the hard coat film and the circularly polarizing functional layer are laminated has a structure of hard coat layer / transparent substrate / circularly polarizing functional layer. The circularly polarizing functional layer has a laminated structure of a PVA polarizer and a retardation layer, and the retardation layer may be a retardation TAC having a retardation function. The retardation TAC can also serve as the TAC constituting the hard coat film. In other words, the structure of the hard coat layer / retardation TAC / PVA polarizer is also generally considered to be the laminate of the present invention. The method for producing the laminate is not particularly limited, but for example, a circularly polarizing functional layer laminate can be formed by adhering the triacetyl cellulose surface of a hard coat film that does not have a hard coat layer to a PVA polarizer. EXAMPLES
[0066] <Weight average molecular weight (Mw)> The weight average molecular weight was measured using a gel permeation chromatography (HLC-8220GPC) manufactured by Tosoh Corporation, and a separation column (TSK-GEL SU PER H5000”, “TSK-GEL SUPER H4000”, “TSK-GEL The polystyrene-equivalent weight average molecular weight was measured using four "TSK-GEL SUPER H3000" and "TSK-GEL SUPER H2000" columns connected in series, using tetrahydrofuran at a temperature of 40°C as the mobile phase, and a flow rate of 0.6 ml / min.
[0067] <Haze value measurement> The haze value was calculated by taking the average value of n=3 measurements with a D65 light source using a spectrophotometer / haze meter "SH 7000" manufactured by Nippon Denshoku Industries Co., Ltd., placed in a temperature and humidity chamber at 23°C and a relative humidity of 50% (50% RH).
[0068] <Transmittance measurement> The obtained composition for forming a hard coat layer was applied onto a transparent substrate using a No. 8 bar coater, and then dried in a hot air oven for 1 minute. The applied layer was then cured by irradiating it with ultraviolet rays from a high-pressure mercury lamp with an output of 80 w / cm, thereby obtaining a hard coat film having a transparent substrate, an active energy ray-curable composition for forming a hard coat layer, and a hard coat layer. The hard coat film having this hard coat layer was measured for transmittance at 380 nm and 420 nm using a spectrophotometer "UH5200" manufactured by Hitachi High-Tech Corporation, placed in a thermo-hygroscopic chamber at 23°C and 50% RH.
[0069] <Difference in transmittance of hard coat film [(tc)-(ta)]> The hard-coated film was immersed in a 9 wt% NaOH aqueous solution at 50°C for 5 minutes, washed with water, and then dried in a box oven at 100°C for 5 minutes, after which the transmittance (tc) at a wavelength of 380 nm was measured. The difference between the transmittance (tc) and the transmittance (ta) at a wavelength of 380 nm of an untreated hard-coated film (not immersed in a sodium hydroxide aqueous solution) was calculated.
[0070] <Production of polyfunctional urethane (meth)acrylate (a1)> (Synthesis Example 1) Urethane acrylate mixed solution (P1): stirrer, reflux condenser, nitrogen inlet tube Into a four-neck flask equipped with a thermometer and a dropping funnel, 1,325.6 parts by mass of ARONIX M306 (manufactured by Toagosei Co., Ltd., a mixture of 67.5% by mass of pentaerythritol triacrylate (PE-3A) (a3-1) having a molecular weight of 298 and 32.5% by mass of pentaerythritol tetraacrylate (PE-4A) (a3-2) having a molecular weight of 352) 0.1 parts by mass of Neostan U-810 (manufactured by Nitto Kasei Co., Ltd., tin catalyst) was added and the liquid temperature was raised to 50°C, after which 1,109.8 parts by mass of Desmodur Z4470BA (manufactured by Sumika Covestro Co., Ltd., non-volatile content 70% by mass (volatile content butyl acetate), containing 85.8% by mass of isophorone diisocyanate (IPDI) trimer having a molecular weight of 667 relative to the non-volatile content, and having a nurate ring with an NCO content of 11.9%) was added dropwise from the dropping funnel over a period of 30 minutes. After the temperature rise subsided, the mixture was heated to 80°C and reacted for 3 hours. After confirming that the isocyanate group peak had disappeared by Fourier transform infrared spectroscopy (FT-IR), the temperature was lowered to room temperature, and a urethane acrylate mixture (P1) was obtained with a non-volatile content of 86.7% by mass, containing 77.1% by mass of urethane acrylate (a1-1) having 9 acryloyl groups and a weight average molecular weight of 1600, 20.8% by mass of pentaerythritol tetraacrylate (PE-4A) (a3-2), and 2.1% by mass of other compounds (e-1) having no (meth)acryloyl groups.
[0071] (Synthesis Example 2) Urethane acrylate mixed solution (P2): stirrer, reflux condenser, nitrogen inlet tube A 4-neck flask equipped with a thermometer and a dropping funnel was fitted with an Aronix M306 1325.6 mass parts of hexane and 0.1 parts by mass of Neostan U-810 were added, the liquid temperature was raised to 50°C, and then 571.7 parts by mass of Duranate TPA-100 (manufactured by Asahi Kasei Corporation, 100% by mass non-volatile content, containing 88.3% by mass of hexamethylene diisocyanate (HDI) trimer having a molecular weight of 505 relative to the non-volatile content, and having a nurate ring with an NCO content of 23.1%) was added dropwise from the dropping funnel over 30 minutes. After the temperature rise subsided, the mixture was heated to 80°C and reacted for 3 hours. After it was confirmed that the isocyanate group peak had disappeared in FT-IR, the temperature was lowered to room temperature, and a urethane acrylate mixture (P2) with a non-volatile content of 100% by mass was obtained, containing 76.1% by mass of urethane acrylate (a1-2) having 9 acryloyl groups and a weight average molecular weight of 1,400, 23.0% by mass of pentaerythritol tetraacrylate (PE-4A) (a3-2), and 0.9% by mass of other compound (e-2) having no (meth)acryloyl groups.
[0072] (Synthesis Example 3) Urethane acrylate mixed solution (P3): stirrer, reflux condenser, nitrogen inlet tube Into a four-neck flask equipped with a thermometer and a dropping funnel, 4439.0 parts by mass of Desmodur Z4470BA, 432.6 parts by mass of cyclohexyldimethanol (molecular weight 144, hydroxyl value 389 mgKOH / g), and Neostan U-810 0.1 parts by mass of 4-hydroxybutyl acrylate (molecular weight 144, hydroxyl value 389 mgKOH / g) was added, the mixture was heated to 80°C, and reacted for 3 hours. After confirming that the peak intensity of the isocyanate group in FT-IR was 50% of that before the reaction, 865.0 parts by mass of 4-hydroxybutyl acrylate (molecular weight 144, hydroxyl value 389 mgKOH / g) was added, and the mixture was reacted for a further 3 hours at 80°C. After confirming that the peak of the isocyanate group had disappeared in FT-IR, the temperature was lowered to room temperature, and a urethane acrylate mixed liquid (P3) with a non-volatile content of 100.0% by mass was obtained, which contained 96.0% by mass of urethane acrylate (a1-3) having 6 acryloyl groups and a weight average molecular weight of 4000, and 4.0% by mass of other compound (e-3) having no (meth)acryloyl group in the non-volatile content.
[0073] <Production of polyfunctional urethane (meth)acrylate (a2)> (Synthesis Example 4) Urethane acrylate mixed solution (Q1): In a four-neck flask equipped with a stirrer, a reflux condenser, a nitrogen inlet tube, a thermometer, and a dropping funnel, 533 parts by mass of Pentaerythritol Triacrylate (manufactured by Thermo Fisher Scientific, pentaerythritol triacrylate (PE-3A), purity 97% or more, molecular weight 298), 237 parts by mass of Aronix M306, and 100.1 parts by mass of Neostan U-8 were added. After the liquid temperature was raised to 50°C, 224 parts by mass of Desmodur I (manufactured by Sumika Covestro Co., Ltd., isophorone diisocyanate (IPDI)) was added dropwise from the dropping funnel over a period of 30 minutes. After the temperature rise subsided, the temperature was raised to 80°C and the reaction was carried out for 3 hours. After confirming that the acryloyl group peaks had disappeared, the temperature was lowered to room temperature, and a urethane acrylate mixture Q1 was obtained, which contained, in the non-volatile matter, 82.6 mass% of urethane acrylate (a2-1) (acryloyl group equivalent 137) having a molecular weight of 900 and six acryloyl groups, 9.7 mass% of pentaerythritol triacrylate (a3-1) (PE-3A, acryloyl group equivalent 99), and 7.7 mass% of pentaerythritol tetraacrylate (a3-2) (PE-4A, acryloyl group equivalent 88).
[0074] (Synthesis Example 5) Urethane acrylate mixed solution (Q2): A 4-neck flask equipped with a stirrer, reflux condenser, nitrogen inlet tube, thermometer, and dropping funnel was charged with Aronix M403 (manufactured by Toagosei Co., Ltd., 2500 parts by mass of a mixture of 55% by mass of dipentaerythritol pentaacrylate (DPPA (a3-3)) with a molecular weight of 524 and 45% by mass of dipentaerythritol hexaacrylate (DPHA (a3-4)) with a molecular weight of 579, and 0.1 parts by mass of Neostan U-810 were added, and the liquid temperature was raised to 50°C. Then, 224 parts by mass of Desmodur I were added dropwise from the dropping funnel over a period of 30 minutes. After the temperature rise subsided, the temperature was raised to 80°C and the reaction was carried out for 3 hours, and the resultant mixture was analyzed by FT-IR. After confirming that the peak of the isocyanate group disappeared, the temperature was lowered to room temperature, and the non-volatile matter contained a urethane acrylate (a2- A urethane acrylate mixed solution (Q2) containing 46.7 mass% of dipentaerythritol pentaacrylate (a3-3) (DPPA, acryloyl group equivalent 127), 12.0 mass% of dipentaerythritol hexaacrylate (a3-4) (DPHA, acryloyl group equivalent 96), and 41.3 mass% of dipentaerythritol hexaacrylate (a3-4) (DPHA, acryloyl group equivalent 96) was obtained.
[0075] The materials used in the examples and comparative examples are described below.
[0076] <Polyfunctional urethane (meth)acrylate (a1)> (a1-1): molecular weight 1600, number of acryloyl groups 9 (a1-2): molecular weight 1400, number of acryloyl groups 9 (a1-3): molecular weight 4000, number of acryloyl groups 6 <Polyfunctional urethane (meth)acrylate (a2)> (a2-1): molecular weight 900, number of acryloyl groups 6 (a2-2): molecular weight 1300, number of acryloyl groups 10 <Polyfunctional (meth)acrylate (a3)> (a3-1): Pentaerythritol triacrylate (PE-3A) (a3-2): Pentaerythritol tetraacrylate (PE-4A) (a3-3): Dipentaerythritol pentaacrylate (DPPA) (a3-4): Dipentaerythritol hexaacrylate (DPHA) Multifunctional acrylate liquid (R1): Aronix M-403 (a mixture of 55% dipentaerythritol pentaacrylate (a3-3) and 45% dipentaerythritol tetraacrylate (a3-4) manufactured by Toagosei Co., Ltd.) Multifunctional acrylate liquid (R2): SARTOMER SR368 (molecular weight 423, number of acryloyl groups 3, (a3-5)) manufactured by Arkema Co., Ltd. Multifunctional acrylate liquid (R3): Negami Chemical Industries Co., Ltd.: Art Resin UN-5507 (molecular weight 17000, number of acryloyl groups 15.5, (a3-6), contains 50% propylene glycol monomethyl ether acetate)
[0077] <UV protection agent (B)> UV protection agent (b-1): BASF TINUVIN477 (hydroxyphenyltriazine type UV protection agent, molecular weight over 300) UV protection agent (b-2): RUVA-93 (benzotriazole-based UV protection agent, molecular weight 323) manufactured by Otsuka Chemical Co., Ltd. UV protection agent (b-3): BASF Uvinul 3050 (benzophenone-based UV protection agent, molecular weight 246) UV protection agent (b-4): Manufacturer: Shin-Nakamura Chemical Co., Ltd. Bananaresin UVA-5080 (benzotriazole-based UV protection agent, molecular weight 40,000 to 60,000)
[0078] <Photopolymerization initiator (C)> (c-1): IGM Resins BV: ESACURE ONE: Oligo[2-hydroxy-2-methyl-[1-(methylvinyl)phenyl]propanone (c-2): Daido Chemical Industry Co., Ltd.: DAIDO UV-CURE APO: diphenyl-2,4,6-trimethylbenzoylphosphine oxide (c-3): BASF Corporation: Irgacure OXE01: 1-[4-(phenylthio)phenyl]octane-1,2-dione = 2-(O-benzoyloxime) (c-4): BASF: Irgacure OXE03: Oxime ester photopolymerization initiator (c-5): IGM Resins BV: Omnirad 907: 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one <Sensitizer (F)> (f): IGM Resins BV: Omnirad DETX: 2,4-diethylthioxanthone
[0079] <Solvent (D)> (d1) n-Butyl acetate (manufactured by Daicel Corporation) (d2) DMC: Dimethyl carbonate (Ube Industries, Ltd.) (d3) MEK: Methyl ethyl ketone (Maruzen Petrochemical Co., Ltd.) (d4) MIBK: Methyl isobutyl ketone (Mitsubishi Chemical Corporation) (d5) PGM: Propylene glycol monomethyl ether (manufactured by Taishin Chemical Co., Ltd.)
[0080] <Transparent base material> PET: Polyethylene terephthalate resin film 50μm thick PMMA: Polymethyl methacrylate resin film 50μm thick PC: 50μm thick polycarbonate resin film COP: Polycycloolefin resin film with a thickness of 50 μm
[0081] <Example 1> Into a flask equipped with a stirrer, (20.9 parts of urethane acrylate liquid (P1), 67.8 parts of urethane acrylate liquid (Q1), 14.4 parts of multifunctional acrylate liquid (R1), 10 parts of ultraviolet ray cutter TINUVIN477 (b-1), 10.0 parts of photopolymerization initiator Irgacure OXE03 (c-4), 35 parts of dimethyl carbonate (d2), 12.2 parts of methyl ethyl ketone (d3), 40 parts of methyl isobutyl ketone (d4), and 10 parts of propylene glycol monomethyl ether (d5) were added and stirred to obtain a hard coat layer forming composition containing the following compounds. Urethane acrylate (a1-1): 14.0 parts Urethane acrylate (a2-1): 56.0 parts Pentaerythritol triacrylate (a3-1): 6.6 parts Pentaerythritol tetraacrylate (a3-2): 9.2 parts Dipentaerythritol pentaacrylate (a3-3): 7.8 parts Dipentaerythritol hexaacrylate (a3-4): 6.4 parts Total of 100 parts of active energy ray curing component (A) Other compounds (e-1): 0.6 parts UV protection agent TINUVIN477(b-1): 10 parts Photopolymerization initiator Irgacure OXE03(c-4): 10 parts n-Butyl acetate (d1): 2.8 parts Dimethyl carbonate (d2): 35.0 parts Methyl ethyl ketone (d3): 12.2 parts Methyl isobutyl ketone (d4): 40.0 parts Propylene glycol monomethyl ether (d5): 10.0 parts
[0082] <Examples 2 to 37 and Comparative Examples 1 to 6> As shown in Tables 1 to 4, the compositions, blend amounts (parts by mass) and transparent substrates were changed, but the experimental results were In the same manner as in Example 1, compositions for forming a hard coat layer of Examples 2 to 37 and Comparative Examples 1 to 6 were prepared. manufactured things. However, Examples 1, 2, 13 to 17, 21 to 23, and 34 to 37 are reference examples.
[0083] The obtained compositions for forming a hard coat layer were evaluated for elution resistance, pencil hardness, adhesion, and warpage by the following methods. The results are shown in Tables 1 to 4.
[0084] [Elution resistance] The obtained composition for forming a hard coat layer was applied to a transparent substrate using a bar coater No. The coating was then applied using a high-pressure mercury lamp with an output of 80 watts / cm, with an accumulated exposure of 400 mJ / cm. 2 The coating layer was cured by irradiating with ultraviolet light to obtain a hard-coated film for evaluating elution resistance having a hard-coat layer with a thickness of 5 to 6 μm. The obtained hard-coated film was cut into test films with a length of 100 mm and a width of 50 mm to prepare test films. This test film was immersed in a 9 wt % aqueous solution of sodium hydroxide heated to 50° C. for 5 minutes, then taken out, washed with water, and dried in a box oven at 100° C. for 2 minutes. The transmittance (ta) and (tc) shown below were measured. (ta): Transmittance at a wavelength of 380 nm of a hard coat film not immersed in a sodium hydroxide aqueous solution (tc): Transmittance of the hard coat film at a wavelength of 380 nm after immersion in an aqueous solution of sodium hydroxide, washing with water and drying. From the obtained (ta) and (tc), (tc)-(ta) was calculated, and the dissolution resistance was evaluated according to the following criteria. Note that Comparative Example 4, which did not contain a UV cut agent, was marked as "-" since it was not possible to evaluate the dissolution resistance. ○:(tc)-(ta)≦1%(good) △: 1%<(tc)-(ta)≦2% (no problem in practical use) ×:2%<(tc)-(ta)(not practical)
[0085] [Pencil hardness] As in the case of [Resistance to Dissolution], a hard-coated film for evaluating pencil hardness was obtained. The pencil hardness of the obtained hard-coated film was measured using pencils of different hardness according to JIS K5400 (199 0) was measured using a test method similar to that described above. ◎: Pencil hardness is 3H or more (excellent) ○: Pencil hardness is H~2H (good) △: Pencil hardness is F (no problem in practical use) ×: Pencil hardness is HB or less (not practical)
[0086] [Adhesion] A hard coat film for evaluating adhesion was obtained in the same manner as in [Elution Resistance]. The surface of the obtained hard coat film opposite to the surface on which the hard coat layer was formed was attached to a glass plate via an adhesive layer having a thickness of about 20 μm, and the surface of the hard coat layer was then subjected to a JIS K5400 test. A cross-cut peel test was carried out and evaluated according to the following criteria. ◎: Peeling count 0 / 100 (Excellent) ○: Peeling count 1-5 / 100 (good) △: Number of peeled off pieces: 6-20 / 100 (no practical problems) ×: Number of peeled pieces: 21-100 / 100 (not practical)
[0087] [Warp test] Similarly to [Elution Resistance], a hard-coated film for warpage test was obtained. The obtained hard-coated film was cut into a length of 100 mm and a width of 50 mm and used as a test film. The mixture was placed in a constant temperature and humidity room at 22°C and 50% RH for 6 hours. The test film was placed on a horizontal plane, and the distance between both ends in the width direction was measured at both ends of the long sides and at three points in the center using a microgauge, and the average value was calculated. ◎: 40mm or more (excellent) ○: 30mm or more and less than 40mm (good) △: 10mm or more and less than 30mm (no practical problems) ×: Cylindrical or less than 10 mm (not practical)
[0088] [Table 1]
[0089] [Table 2]
[0090] [Table 3]
[0091] [Table 4]
[0092] As shown in Tables 1 to 4, by using the composition for forming a hard coat layer of the present invention, it is possible to provide a hard coat film having a hard coat layer that has high UV protection properties, reduces the elution of the UV protection agent during the saponification process, prevents a decrease in the UV protection properties of the coating film and contamination of the saponification treatment solution, improves the efficiency of the display production process by reducing curling, and prevents scratches during the display production process by imparting high hard coat properties.
Claims
1. The composition comprises an active energy ray-curable component (A), an ultraviolet ray blocking agent (B), a photopolymerization initiator (C) and a solvent (D), The active energy ray-curable component (A) contains all of the following (a1), (a2), and (a3): The molecular weight of the ultraviolet ray blocking agent (B) is 300 or more, The photopolymerization initiator (C) contains at least one of an oxime ester compound and a phosphine oxide compound. An active energy ray-curable composition for forming a hard coat layer on a transparent substrate. (a1) A polyfunctional urethane (meth)acrylate having six or more (meth)acryloyl groups and a nurate ring skeleton. (a2) A polyfunctional urethane (meth)acrylate having 4 to 15 (meth)acryloyl groups and a weight average molecular weight of 500 to 15,000 (excluding (a1)). (a3) Other polyfunctional (meth)acrylates
2. A hard coat film having a hard coat layer which is a cured product of the active energy ray-curable composition according to claim 1 on a transparent substrate.
3. 3. The hard coat film according to claim 2, which has a transmittance (ta) at a wavelength of 380 nm of 4% or less and a transmittance (tb) at a wavelength of 420 nm of 70% or more.
4. The hard coat film according to claim 3, which satisfies the following formula (2): Formula (2) (tc)-(ta)≦1% (ta): Transmittance at a wavelength of 380 nm of a hard coat film not immersed in an aqueous sodium hydroxide solution (tc): Transmittance of the hard coat film at a wavelength of 380 nm after immersion in an aqueous sodium hydroxide solution, washing with water and drying.
5. A laminate comprising the hard coat film according to any one of claims 2 to 4 and a circularly polarizing functional layer.
Citation Information
Patent Citations
Selective alkali saponification process for triacetyl cellulose film and production apparatus therefor
JP2007308670A
Transparent double-sided adhesive sheet for image display device, and image display device
JP2012211305A
Polarizing film with pressure-sensitive adhesive layer, and image display device
JP2022000694A
Actinic-ray-curable resin composition, cured object, layered product, and article
WO2020209264A1